2016 IEEE NetSoft Conference and Workshops (NetSoft) 2016
DOI: 10.1109/netsoft.2016.7502423
|View full text |Cite
|
Sign up to set email alerts
|

Self-modeling based diagnosis of services over programmable networks

Abstract: Abstract-In this paper, we propose a multi-layer self-diagnosis framework for networking services within SDN and NFV environments. The framework encompasses three main contributions: 1) the definition of multi-layered templates to identify what to supervise while taking into account the physical, logical, virtual and service layers. These templates are also finergranular, extendable and machine-readable; 2) a self-modeling module that takes as input these templates, instantiates them and generates on-the-fly t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…This is the reason why we conceive a self‐diagnosis approach that meets the following criteria: Multilayer self‐diagnosis: We propose a framework to diagnose network services over the combined NFV and SDN environments, which, to the best of our knowledge, has not been tackled before. In this paper, we extend our previous work, by diagnosing and correlating more layers, i.e., virtual and services layers, while considering their dynamic dependencies with the underlying logical and physical resources. Our approach utilizes a probabilistic and multilayered dependency graph, like Bahl and Hounkonnou .…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…This is the reason why we conceive a self‐diagnosis approach that meets the following criteria: Multilayer self‐diagnosis: We propose a framework to diagnose network services over the combined NFV and SDN environments, which, to the best of our knowledge, has not been tackled before. In this paper, we extend our previous work, by diagnosing and correlating more layers, i.e., virtual and services layers, while considering their dynamic dependencies with the underlying logical and physical resources. Our approach utilizes a probabilistic and multilayered dependency graph, like Bahl and Hounkonnou .…”
Section: Related Workmentioning
confidence: 99%
“…In this case, the self‐diagnosis mechanism deals with all equipment involved in the network, mixing faults, or failures affecting clients and other nonimpacting faults. In our previous work, we introduced a self‐diagnosis framework that generated on‐the‐fly the dependency graph from the network topology and the logical resources running on top of the nodes. The impact of faulty physical and logical nodes on services was not studied.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…They demonstrated that the proposed method is applicable to two usecases of memory-leak and network congestion in NFV system. Sanchez et al [170] (2016) A multi-layer self-diagnosis framework for networking services in SDN and NFV environments.…”
Section: Trouble Shootingmentioning
confidence: 99%
“…They demonstrated that the proposed function is applicable to two use cases of memoryleak and network congestion in an NFV system. Sanchez et al [170] proposed a multi-layer selfdiagnosis framework for networking services in SDN and NFV environments. Their framework consists of a (1) multilayered template, (2) self-modeling module, and (3) rootcause analysis (RCA) module.…”
Section: Trouble Shootingmentioning
confidence: 99%